Polyvinyl alcohol film, and polarizing film and polarizing plate using the same
Patent Information
- Application Number
- CN202180088168.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-28
- Filing Date
- 2021-12-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-12-28
AI Technical Summary
[0024]根据本发明,可提供与以往相比更不易观察到拉伸加工后的偏振板不均的PVA膜以及使用这种PVA膜的偏振膜和偏振板。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004308608020000041
Abstract
Description
Technical Field
[0001] This invention relates to polyvinyl alcohol films and polarizing films and polarizing plates using the same. Background Technology
[0002] A polarizing plate, which has both light-transmitting and light-blocking functions, and a liquid crystal, which changes the polarization state of light, are both fundamental components of a liquid crystal display (LCD). LCDs are widely used in small devices such as calculators and watches, laptops, LCD monitors, LCD color projectors, LCD televisions, car navigation systems, mobile phones, and measuring devices used indoors and outdoors.
[0003] Polarizing plates are generally manufactured as follows: A polyvinyl alcohol (PVA) film (hereinafter sometimes abbreviated as "PVA") is dyed, uniaxially stretched, and further fixed using boron compounds or similar substances to create a polarizing film. A protective film, such as a cellulose triacetate (TAC) film, is then adhered to the surface of this polarizing film. In recent years, the demand for energy-efficient LCDs has also led to higher transmittance requirements for polarizing plates. With the increasing transmittance of polarizing plates, unevenness caused by the uneven thickness of the PVA film, which was previously unobservable, has become apparent, necessitating PVA films with superior flatness compared to previous products.
[0004] Patent document 1 describes a method for manufacturing a PVA film with superior flatness compared to the past, by using an air knife to suppress variations in the flow delay.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2017-008298 Summary of the Invention
[0008] The problem that the invention aims to solve
[0009] However, in Patent Document 1, although better film thickness flatness in the MD direction can be obtained compared with the past, there is a problem: since the thin part of the film is concentrated in the width direction, the stress is concentrated in the thin part of the film. Although the observation is low, regular polarization plate inhomogeneity can still be observed, which cannot meet the requirements of further high transmittance of LCD.
[0010] Therefore, the object of the present invention is to provide a PVA film in which the unevenness of the polarizer during stretching is not easily observed even when the LCD achieves further high transmittance, and a polarizer and polarizer using such a PVA film.
[0011] Methods for solving problems
[0012] Through repeated and in-depth research, the inventors discovered that by further reducing the film thickness unevenness in the MD direction (flow direction) of the PVA film, and adjusting the phase deviation of the film thickness unevenness at a specific position in the TD direction (width direction) to a specific range, the above-mentioned problem can be achieved. Based on this discovery, further repeated research was conducted, and thus the present invention was completed.
[0013] That is, the present invention is:
[0014] [1] Polyvinyl alcohol film, wherein the film thickness profile of any point F0 on the film surface is defined as F0(x), and the film thickness profile of the point from F0 towards TD direction -100mm is defined as F... -100 (x), the film thickness profile at a point 200mm from F0 in the TD direction is defined as F. -200 (x), the film thickness profile at a point 100mm from F0 in the TD direction is defined as F. +100 (x), the film thickness profile of the point 200mm from F0 in the TD direction is set as F. +200 When (x), the tilt values of the MD direction of each film thickness profile, i.e., F′0(x) and F′, are used. -100 (x), F′ -200 (x), F′ +100 (x) and F′ +200 The average tilt value of the average representation of F′0(x) in the MD direction is below 0.02. Let C be the point where F′0(x) shows a minimum value. n |F′ when (n=1, 2, 3…) -100 (C n )-F′0(C n )|、|F′ -200 (C n )-F′0(C n )|、|F′ +100 (C n )-F′0(C n )| and |F′ +200 (C n )-F′0(C n The phase parameter defined by the average value of | is greater than 0.015;
[0015] [2] The polyvinyl alcohol film described in [1] above has a width of 4m or more;
[0016] [3] The polyvinyl alcohol film according to [1] or [2] above has a swelling degree of 170 to 220%;
[0017] [4] The polyvinyl alcohol film according to any one of [1] to [3] above has a thickness of 30 μm to 65 μm;
[0018] [5] The polyvinyl alcohol film according to any one of the preceding [1] to [4], which is a film for producing an optical film;
[0019] [6] The polyvinyl alcohol film according to the preceding [5], wherein the optical film is a polarizing film;
[0020] [7] A polarizing film, which is produced using the polyvinyl alcohol film according to any one of the preceding [1] to [6];
[0021] [8] A polarizing plate, which is produced by attaching a protective film to at least one surface of the polarizing film according to the preceding [7];
[0022] [9] A method for producing a polyvinyl alcohol film, comprising the step of forming a polyvinyl alcohol film using an aqueous polyvinyl alcohol solution having a concentration of 32% by mass or less, and stretching the polyvinyl alcohol film at a draw ratio of 1.075 to 1.135 when the moisture content of the polyvinyl alcohol film is 20% by mass or more.
[0023] 】Advantageous Effects of Invention
[0024] According to the present invention, it is possible to provide a PVA film in which unevenness of a stretched polarizing plate is less likely to be observed as compared with conventional ones, as well as a polarizing film and a polarizing plate using such a PVA film.
[0025] Hereinafter, the present invention will be specifically described.
[0026] <Film thickness measurement of PVA film>
[0027] The film thickness measurement of the PVA film in the present invention is carried out under the following conditions. From the viewpoint of phase contrast of the film thickness in the width direction, the measurement must be performed using a two-dimensional film thickness meter.
[0028] <Apparatus used> Line scan film thickness meter (TI-750HR-1: manufactured by Otsuka Electronics Co., Ltd.)
[0029] <Measurement interval> MD: 1 mm TD: 1 mm
[0030] <Measured MD length> 1024 mm
[0031] <Measured TD length> 750 mm per scan
[0032] (Average tilt value in MD direction)
[0033] The PVA film of the present invention is characterized in that the average tilt value in the MD direction (hereinafter referred to as MD average tilt value) is 0.02 μm / mm or less. The MD average tilt value is more preferably 0.018 μm / mm or less. Hereinafter, a detailed calculation method for the MD average tilt value will be described.
[0034] Based on the two-dimensional film thickness profile obtained using a line-scan film thickness gauge, with any point on the PVA film set to position 0mm, the film thickness profiles at positions +100mm, +200mm, -100mm, and -200mm (positive and negative directions are arbitrary) along the TD direction from that arbitrary point are smoothed using an 8pt FFT, and the resulting value is set as F. +100 (x), F +200 (x), F -100 (x) and F -200 (x). Additionally, the film thickness profile at the point with position 0 mm is set as F0(x). Here, the subscripts "0", "+100", "+200", "-100", and "-200" represent the position in the TD direction, and x represents the position in the MD direction. In other words, regarding x, when a certain point is set to 0 mm, the film thickness profile of 1024 points is measured every 1 mm along the MD direction, from 1 mm to 1024 mm. For positions starting from any of the aforementioned points and moving towards 0 mm, +100 mm, +200 mm, -100 mm, and -200 mm in the TD direction, the film thickness profile of these 1024 points is measured respectively. It should be noted that, here, the measurement interval in the MD direction and the number of points along the MD direction for measuring the film thickness profile of 1024 points every 1 mm can be appropriately designed.
[0035] The average tilt value of the MD in this invention is calculated using the following equations (1) to (6). The film thickness data at each 1mm point along a 1024mm section in the MD direction is differentiated. The absolute value of this differentiation is averaged across the 1024 points, and the average value of five line segments is calculated. This value is defined as the average tilt value of the MD. The average tilt value of the MD is a numerical value representing the intensity of film thickness non-uniformity in the MD direction; a larger value indicates greater film thickness non-uniformity. It should be noted that F0(x), F... +100 (x), F +200 (x), F -100 (x), F -200 The differential values of (x) can be expressed as F′0(x) and F′ respectively. +100 (x), F′ +200 (x), F′ -100 (x), F′ -200 (x).
[0036] [Mathematical Expression 1]
[0037]
[0038]
[0039]
[0040]
[0041]
[0042]
[0043] It should be noted that k in equations (1) to (6) represents a function of x, i.e., F′0(x), F′ +100 (x), F′ +200 (x), F′ -100 (x), F′ -200 Substitute the symbols from 1 to 1024 into x in (x).
[0044] F0(x), F +100 (x), F +200 (x), F -100 (x), F -200 The differential values of F0(x) are defined as these slope values. For example, the slope value can also be defined as the difference between F0(x) and F0(x+1) divided by the distance between point x and point (x+1). +100 (x), F +200 (x), F -100 (x), F -200 In the case of (x), the difference between the film thickness profile of point x and point (x+1) can also be divided by the distance between point x and point (x+1) to obtain the tilt value.
[0045] The average tilt value of the PVA film of the present invention, calculated according to the above formula, must be 0.02 μm / mm or less, preferably 0.019 μm / mm or less, and more preferably 0.016 or less. If the average tilt value of the MD is greater than 0.02, polarization unevenness during the processing of the polarizing plate will be strongly observed, which will impair the display quality of the LCD.
[0046] Furthermore, the average MD tilt value (c) of the PVA film at position +200mm calculated according to the above formula is preferably 0.019 μm / mm or less, more preferably 0.016 μm / mm or less. Similarly, the average MD tilt value (e) at position -200mm is preferably 0.019 μm / mm or less, more preferably 0.016 μm / mm or less.
[0047] There are no particular limitations on the method for obtaining a PVA film with an average tilt value of 0.02 or less. For example, a method for manufacturing a PVA film is to form a polyvinyl alcohol film by using an aqueous solution of polyvinyl alcohol with a concentration of 32% by mass or less, and to stretch the polyvinyl alcohol film at a stretch ratio of 1.075 to 1.135 when the moisture content of the polyvinyl alcohol film is 20% by mass or more.
[0048] <Phase parameter (θ)>
[0049] The PVA film of the present invention is characterized in that it simultaneously satisfies the following definition: a phase parameter (θ) of 0.015 μm / mm or more and an average tilt value of MD of 0.02 or less. More preferably, the phase parameter (θ) is 0.016 μm / mm or more.
[0050] The phase parameter (θ) in this invention is a value defined by the following formula. In the following formula, C... n This refers to: for |F′0(C n The point that reaches its minimum is labeled C1, C2, C3…C1, starting upstream in the MD direction. n The number. |F′0(C n The number of points that reach the minimum is less than the number of points that reach 1024.
[0051] [Mathematical Expression 2]
[0052] α(C n )=F′ +100 (C n )-F′0(C n (Equation 7)
[0053] β(C n )=F′ +200 (C n )-F′0(C n (Equation 8)
[0054] γ(C n )=F′ -100 (C n )-F′0(C n (Equation 9)
[0055] δ(C n )=F′ -200 (C n )-F′0(C n (Equation 10)
[0056]
[0057]
[0058] It should be noted that k in (Equation 12) represents the value of C. n The function is λ(C) n ) for C n Substitute C1 to C1 respectively n The symbol.
[0059] The phase parameter (θ) in this invention refers to the parameter representing the consistency of the position of the node that causes the film thickness unevenness at the position of 0 mm in the TD direction with the node that causes the film thickness unevenness at the four positions that are offset from this position in the TD direction in the MD direction. The larger the value, the less uniform the nodes that cause the film thickness unevenness at the five points in the width direction are, and the less likely film thickness unevenness will occur.
[0060] The phase parameter (θ) of the PVA film of the present invention, calculated according to the above formula, must be 0.015 or higher, preferably 0.0153 or higher. If the phase parameter (θ) is less than 0.015, stress concentration will occur during stretching due to the concentration of nodal positions in the width direction of the PVA film, and after stretching, a regular polarization plate unevenness extending along the width direction will be observed.
[0061] There are no particular limitations on the method for obtaining a PVA film with a phase parameter (θ) of 0.015 or higher. For example, a method for manufacturing a PVA film is to form a polyvinyl alcohol film by using an aqueous solution of polyvinyl alcohol with a concentration of 32% by mass or less, and to stretch the polyvinyl alcohol film at a stretch ratio of 1.075 to 1.135 when the moisture content of the polyvinyl alcohol film is 20% by mass or more.
[0062] The average tilt value of the MD on the surface of the PVA film of the present invention is less than 0.02 and the phase parameter (θ) is greater than or equal to 0.014. However, the average tilt value of the MD on at least one surface of the PVA film may be less than 0.02 and the phase parameter (θ) may be greater than or equal to 0.014. Alternatively, the average tilt value of the MD on at least two surfaces of the PVA film may be less than 0.02 and the phase parameter (θ) may be greater than or equal to 0.014.
[0063] From the viewpoint of use in large-format LCD televisions, the width of the PVA film of the present invention is preferably 4 m or more, more preferably 4.5 m or more. On the other hand, if the width of the PVA film is too large, uniaxial stretching itself becomes difficult to achieve uniformly when using a practically available device to manufacture the polarizing film. Therefore, the width of the PVA film is preferably 7 m or less.
[0064] The swelling degree of the PVA film of the present invention is preferably 170% or more, more preferably 180% or more. The swelling degree of the PVA film is preferably 220% or less, more preferably 210% or less. If the swelling degree is less than 170%, there is a tendency for uneven swelling to occur, resulting in uneven dyeing during dyeing. If the swelling degree is greater than 220%, there is a tendency for wrinkles to form during the process, which is not preferred. As a method to adjust the swelling degree of the PVA film to these ranges, for example, a method of appropriately adjusting the heat treatment temperature of the PVA film after drying can be cited.
[0065] Swelling degree is an indicator of the water retention capacity of a PVA film when it is immersed in water. It can be calculated as a percentage by dividing the mass of the PVA film after immersion in water at 30°C for 30 minutes by the mass after drying at 105°C for 16 hours.
[0066] The volatile content of the film-forming solution used in the formation of the PVA film of the present invention is preferably 70% by mass or more, more preferably 71% by mass or more. If the volatile content of the PVA aqueous solution used for film formation is less than 70% by mass, the effect of reducing film thickness unevenness due to the leveling effect during casting cannot be expected, and the average tilt value of MD becomes higher, which is not preferred. If the volatile content of the film-forming solution of the PVA aqueous solution is too high, the drying time increases and the productivity decreases, which is also not preferred.
[0067] Here, the "volatile fraction of the film-forming stock solution" in this invention refers to the volatile fraction calculated by the following formula.
[0068] The volatile fraction (mass%) of the film-forming solution = {(Wa-Wb) / Wa} × 100
[0069] (In the formula, Wa represents the mass (g) of the film-forming stock solution, and Wb represents the mass (g) of Wa(g) film-forming stock solution after drying in an electric dryer at 105℃ for 16 hours.)
[0070] As for the conditions for forming the PVA film of the present invention, it is preferred that the stretching ratio is set to 1.075 or higher when the moisture content of the PVA aqueous solution used for film formation is 20% by mass or higher, and more preferably 1.08 or higher. It is also preferred that the stretching ratio is set to 1.135 or lower when the moisture content of the PVA aqueous solution used for film formation is 20% by mass or higher, more preferably less than 1.13, and even more preferably less than 1.12. Generally, the stretching ratio is controlled by the speed ratio of the transport rollers. The larger the stretching ratio, the lower the ultimate stretch ratio during stretching, and the higher the probability of stretching breakage during stretching. Therefore, when the stretching ratio is 1.12 or higher, a process to mitigate the influence of the stretching ratio is sometimes required. Furthermore, if the stretching ratio is higher than 1.135, the ultimate stretch ratio during stretching is significantly reduced, which is not preferred. Furthermore, if the draw ratio is less than 1.075, the phase parameter (θ) becomes smaller, which is not preferable from the viewpoint of observing the inhomogeneity of the polarizer. Additionally, as a condition for manufacturing PVA film, the moisture content during drawing is preferably 20% by mass or more, more preferably 22% by mass or more. If the moisture content during drawing is less than 20% by mass, it is difficult to increase the phase parameter (θ). For the above reasons, it is necessary to set the moisture content and draw ratio during drawing within the aforementioned ranges.
[0071] (PVA)
[0072] As the PVA resin included in the PVA film of the present invention, examples include resins obtained by saponifying polyvinyl esters obtained by polymerizing one or more vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl pentanoate, vinyl tert-carboxylate, vinyl laurate, vinyl stearate, vinyl benzoate, and isopropylene acetate. Among the aforementioned vinyl esters, vinyl acetate is preferred from the viewpoints of ease of PVA manufacturing, ease of acquisition, and cost.
[0073] PVA can be modified using one or more graft copolymerizable monomers, provided that the effects of the present invention are not impaired. Examples of such graft copolymerizable monomers include, for instance, unsaturated carboxylic acids or their derivatives; unsaturated sulfonic acids or their derivatives; and α-olefins with 2 to 30 carbon atoms. The proportion of structural units derived from graft copolymerizable monomers in PVA is preferably 5 mol% or less, depending on the total molar number of all structural units constituting the PVA.
[0074] Some of the hydroxyl groups in PVA may be cross-linked or not. Furthermore, some of the hydroxyl groups in the aforementioned PVA may react with aldehyde compounds such as acetaldehyde and butyraldehyde to form an acetal structure, or they may not react with these compounds to form an acetal structure.
[0075] The degree of polymerization of PVA is preferably 2000 or more, more preferably 2200 or more, and even more preferably 2400 or more. When the degree of polymerization is less than 2000, the durability of the resulting polarizing film tends to decrease. The degree of polymerization of PVA is preferably 2700 or less, more preferably 2650 or less, and even more preferably 2600 or less. On the other hand, when the degree of polymerization exceeds 2700, the manufacturing cost tends to increase and the process passability during film formation deteriorates. It should be noted that the degree of polymerization of PVA mentioned in this specification refers to the average degree of polymerization measured according to JIS K 6726-1994.
[0076] From the viewpoint of the water resistance of the polarizing film, the degree of saponification of PVA is preferably 98 mol% or more, more preferably 98.5 mol% or more, and even more preferably 99 mol% or more. If the degree of saponification is less than 98 mol%, the water resistance of the resulting polarizing film tends to deteriorate. It should be noted that the degree of saponification of PVA in this specification refers to the proportion (mol%) of the number of moles of the vinyl alcohol unit relative to the total number of moles of the structural units (typically vinyl ester units) and vinyl alcohol units that can be converted into vinyl alcohol units through saponification. The degree of saponification can be measured according to the description in JIS K6726-1994.
[0077] (Plasticizer)
[0078] The PVA film of the present invention preferably contains a plasticizer. Examples of plasticizers include ethylene glycol, glycerin, propylene glycol, diethylene glycol, diglycerin, triethylene glycol, tetraethylene glycol, trimethylolpropane, and other polyols. The PVA film of the present invention may contain one or more of these plasticizers. Among these, glycerin is preferred from the viewpoint of improving tensile strength.
[0079] The plasticizer content in the PVA film of the present invention is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, relative to 100 parts by mass of PVA contained therein. By making the plasticizer content 1 part by mass or more, the tensile strength of the PVA film can be further improved. On the other hand, the plasticizer content in the PVA film is preferably 20 parts by mass or less, more preferably 17 parts by mass or less, and even more preferably 15 parts by mass or less, relative to 100 parts by mass of PVA. By making the plasticizer content 20 parts by mass or less, it is possible to prevent the PVA film from becoming too soft and reducing its processability.
[0080] (surfactant)
[0081] The PVA film of the present invention preferably contains a surfactant. By using a film-forming solution containing a surfactant to manufacture the PVA film, the film-forming properties of the PVA film are improved. As a result, uneven thickness of the PVA film can be suppressed, and the PVA film can be easily peeled off from the metal rollers and belts used for film formation. When the PVA film is manufactured from a film-forming solution containing a surfactant, the resulting PVA film contains the surfactant.
[0082] There is no particular limitation on the type of surfactant, but from the viewpoint of peelability of PVA film from metal rollers and belts, anionic surfactants and nonionic surfactants are preferred.
[0083] As anionic surfactants, suitable types include carboxylic acid surfactants such as potassium lauryl ether sulfate; sulfate ester surfactants such as polyoxyethylene lauryl ether sulfate and octyl sulfate; and sulfonic acid surfactants such as dodecylbenzene sulfonate.
[0084] As a nonionic surfactant, it is suitable for, for example, alkyl ethers such as polyoxyethylene oleyl ether; alkyl phenyl ethers such as polyoxyethylene octylphenyl ether; alkyl esters such as polyoxyethylene lauryl ester; alkylamines such as polyoxyethylene lauryl amino ether; alkylamides such as polyoxyethylene laurylamide; polypropylene glycol ethers such as polyoxyethylene polyoxypropylene ether; alkanolamides such as oleic acid diethanolamide; and allyl phenyl ethers such as polyoxyalkylene allylphenyl ether.
[0085] These surfactants can be used alone or in combination of two or more.
[0086] The lower limit of the surfactant content in the PVA film of the present invention is preferably 0.01 parts by weight, more preferably 0.02 parts by weight, and even more preferably 0.05 parts by weight, relative to 100 parts by weight of PVA. By setting the surfactant content to the above-mentioned lower limit or above, the film-forming properties and peelability of the PVA film are further improved. On the other hand, the upper limit of the surfactant content in the PVA film is preferably 0.5 parts by weight, more preferably 0.3 parts by weight, and even more preferably 0.2 parts by weight, relative to 100 parts by weight of PVA. By setting the surfactant content to the above-mentioned upper limit or below, it is possible to suppress the surfactant from seeping to the surface of the PVA film, thereby preventing adhesion and reduced processability.
[0087] (Other ingredients)
[0088] The PVA film of the present invention may further contain antioxidants, antifreeze agents, pH adjusters, masking agents, anti-staining agents, oils, surfactants (described later), etc., as needed.
[0089] (shape, etc.)
[0090] The shape of the PVA film of the present invention is not particularly limited, and a long-length film is preferred. Thereby, a more uniform PVA film can be continuously and easily produced, and it can also be continuously used in cases such as when producing a polarizing film using the same. The length of the long-length film (the length in the longitudinal direction) is not particularly limited, and can be appropriately set according to the application and the like, and can be set, for example, within the range of 5 to 30000 m.
[0091] The thickness of the PVA film of the present invention is preferably 30 to 65 μm. If the thickness of the PVA film is less than 30 μm, the processability during stretching deteriorates, and if the thickness of the PVA film is more than 65 μm, it is not preferable for a polarizing plate for thin displays.
[0092] <Method for producing PVA film>
[0093] In the present invention, the method for producing the PVA film is not particularly limited, and the following methods can be adopted: a film forming method using a film-forming stock solution obtained by adding a solvent, additives and the like to PVA and homogenizing the same, by a casting film forming method, a wet film forming method (ejecting into a poor solvent), a dry-wet film forming method, a gel film forming method (a method of temporarily cooling and gelling the film-forming stock solution, then extracting and removing the solvent to obtain a PVA film), or a combination thereof; a melt extrusion film forming method in which the above-mentioned film-forming stock solution is obtained using an extruder or the like, and extruded from a T-die or the like to form a film; any method such as an inflation molding method. Among these, the casting film forming method and the melt extrusion film forming method are preferred because a homogeneous film can be obtained with good productivity. Hereinafter, the casting film forming method or the melt extrusion film forming method for the PVA film will be described.
[0094] Examples of the method for producing a polyvinyl alcohol film of the present invention include the following method for producing a polyvinyl alcohol film, which has a step of forming a polyvinyl alcohol film using a polyvinyl alcohol aqueous solution having a concentration of 32% by mass or less, and stretching the polyvinyl alcohol film at a stretching ratio of 1.075 to 1.135 when the moisture content of the polyvinyl alcohol film is 20% by mass or more. By adopting this production method, a film free from thickness unevenness can be produced.
[0095] In the case where the ultimate stretching ratio is lowered, a step of alleviating the influence of the above-mentioned stretching ratio may be added. As specific methods for alleviating the influence of the stretching ratio, the following can be considered: a method of irradiating the polyvinyl alcohol film with infrared rays or microwaves; a method of reducing the stretching ratio and the cumulative stretching ratio (the product of the stretching ratios when stretching is performed a plurality of times) when the moisture content of the polyvinyl alcohol film is 15 to 5% by mass; a method of applying a plasticizer after stretching; a method of drying using superheated steam; a method of drying at a high temperature; a method of performing heat treatment using a suspension dryer, and the like, any method can be adopted, each method can be combined, and the treatment can be performed a plurality of times.
[0096] When manufacturing PVA films using casting or melt extrusion methods, the aforementioned film-forming solution is cast into a film on a support such as a metal roller or metal strip and heated to remove the solvent, thereby solidifying the film. The solidified film is peeled off from the support, dried as needed using a drying roller or drying oven, and further heat-treated and wound up as needed, thereby obtaining a roll of long strip PVA film.
[0097] There are no particular limitations on the method of adjusting the film-forming solution. Examples include: dissolving PVA and additives such as plasticizers and surfactants in a dissolving tank; or melting and mixing PVA in a aqueous state with plasticizers and surfactants when using a single-screw or twin-screw extruder.
[0098] Examples of liquid media used for preparing film-forming solutions include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, and diethylenetriamine. One or more of these can be used. From the perspective of environmental impact and recyclability, water is the most suitable choice.
[0099] After drying, the PVA film can be further heat-treated as needed. Heat treatment allows for adjustments to the PVA film's strength, swelling degree, birefringence, and other properties. The surface temperature of the heat treatment roller used for heat treatment is preferably 60°C or higher. Furthermore, the surface temperature of the heat treatment roller is preferably 135°C or lower, more preferably 130°C or lower. If the surface temperature of the heat treatment roller is too high, excessive heat is applied, causing the size of the lamellar crystals in the PVA film to increase, making it difficult for the swelling degree of the PVA film to meet the aforementioned range.
[0100] The PVA film manufactured in this way can be further subjected to moisture conditioning treatment, cutting of both ends (edges) of the film, etc., as needed, and then rolled into a roll on a cylindrical core for moisture-proof packaging to form a finished product.
[0101] The volatile content of the PVA film obtained through the above series of processes is not necessarily limited. The volatile content of the final PVA film is preferably 1% by mass or more, more preferably 2% by mass or more. The volatile content of the final PVA film is preferably 5% by mass or less, more preferably 4% by mass or less.
[0102] The thickness unevenness in the MD direction of the PVA film of the present invention is reduced, and the phase deviation of the thickness unevenness in the TD direction is adjusted to a specific range. Therefore, it can be suitable for use as a film in the manufacture of optical films. Here, examples of optical films, such as polarizing films, field-of-view improvement films, phase difference films, and brightness enhancement films, are given below, with polarizing films being preferred. Compared with conventional films, the polarizing film of the present invention, made using the PVA film of the present invention, is less prone to observing unevenness in the polarizing plate after stretching.
[0103] <Methods for manufacturing optical films>
[0104] The following is an example of a method for manufacturing an optical film, and a method for manufacturing a polarizing film will be described in detail.
[0105] Polarizing films typically use PVA film as the base material and are manufactured through processes such as swelling, dyeing, crosslinking, stretching, and fixation. Specific examples of the processing solutions used in each process include the swelling solution used in the swelling process, the dyeing solution used in the dyeing process, the crosslinking solution used in the crosslinking process, the stretching solution used in the stretching process, the fixation solution used in the fixation process, and the cleaning solution used in the cleaning process.
[0106] The following describes the various processing steps that can be used in the manufacturing method for polarizing films. It should be noted that in the manufacturing method for polarizing films, one or more of the following processes may be omitted, the same process may be performed multiple times, and other processes may be performed simultaneously.
[0107] (Cleaning process)
[0108] Before performing swelling treatment on the PVA film, it is preferable to clean the PVA film. This pre-swelling cleaning removes anti-adhesion agents and other substances adhering to the PVA film, preventing contamination of the processing solutions in the polarization film manufacturing process by these agents. Cleaning is preferably performed by immersing the PVA film in a cleaning solution, or by blowing the cleaning solution onto the PVA film. Water, for example, can be used as the cleaning solution. The temperature of the cleaning solution is preferably 20°C or higher, more preferably 22°C or higher, even more preferably 24°C or higher, and particularly preferably 26°C or higher. Maintaining the temperature of the cleaning solution at 20°C or higher facilitates the removal of anti-adhesion agents and other substances adhering to the PVA film. The temperature of the cleaning solution is preferably 40°C or lower, more preferably 38°C or lower, even more preferably 36°C or lower, and particularly preferably 34°C or lower. Furthermore, maintaining the temperature of the cleaning solution at 40°C or lower prevents partial dissolution of the PVA film surface, which could lead to film adhesion and reduced processability.
[0109] (Swelling treatment)
[0110] Swelling treatment can be performed by immersing the PVA film in a swelling treatment solution such as water. The temperature of the swelling treatment solution is preferably 20°C or higher, more preferably 22°C or higher, and even more preferably 24°C or higher. The temperature of the swelling treatment solution is preferably 40°C or lower, more preferably 38°C or lower, and even more preferably 36°C or lower. Furthermore, the immersion time in the swelling treatment solution is preferably 0.1 minutes or higher, more preferably 0.5 minutes or higher. Additionally, the immersion time in the swelling treatment solution is preferably 5 minutes or lower, more preferably 3 minutes or lower. It should be noted that the water used as the swelling treatment solution is not limited to pure water; it can be an aqueous solution containing various components such as boron compounds, or a mixture of water and an aqueous medium. The type of boron compound is not particularly limited; from a processability point of view, boric acid or borax is preferred. When the swelling treatment solution contains a boron compound, from the viewpoint of improving the stretchability of the PVA film, its concentration is preferably 6% by mass or lower.
[0111] (Staining treatment)
[0112] The dyeing process can be performed using iodine-based dyes as dichroic dyes. The dyeing stage can be any period before, during, or after the stretching treatment. Preferably, the dyeing process is performed by immersing the PVA film in a solution containing iodine and potassium iodide (suitably an aqueous solution). The concentration of iodine in the dyeing solution is preferably in the range of 0.005 to 0.2% by mass, and the potassium iodide / iodine (by mass) ratio is preferably in the range of 20 to 100. The temperature of the dyeing solution is preferably 20°C or higher, more preferably 25°C or higher. The temperature of the dyeing solution is preferably 50°C or lower, more preferably 40°C or lower. The dyeing solution may contain boron-containing compounds such as boric acid as crosslinking agents. It should be noted that if the PVA film used as a raw material film already contains a dichroic dye, the dyeing process can be omitted. Furthermore, the PVA film used as a raw material film may also already contain boron-containing compounds such as boric acid or borax.
[0113] (Cross-linking treatment)
[0114] In manufacturing polarizing films, for the purpose of firmly adsorbing dichroic dyes onto the PVA film, it is preferable to perform a crosslinking treatment after dyeing. The crosslinking treatment can be performed by immersing the PVA film in a solution containing a crosslinking agent (suitably an aqueous solution). One or more boron-containing compounds, such as boric acid and borax, can be used as the crosslinking agent. If the concentration of the crosslinking agent in the crosslinking treatment solution is too high, there is a tendency for the crosslinking reaction to over-progress, making it difficult to achieve sufficient stretching in the subsequent stretching process; conversely, if the concentration is too low, the effectiveness of the crosslinking treatment tends to decrease. The concentration of the crosslinking agent in the crosslinking treatment solution is preferably 1% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2% by mass or more. The concentration of the crosslinking agent in the crosslinking treatment solution is preferably 6% by mass or less, more preferably 5.5% by mass or less, and even more preferably 5% by mass or less.
[0115] To suppress the dissolution of dichroic dyes from the dyed PVA film, the crosslinking treatment solution may contain iodine-containing compounds such as potassium iodide. If the concentration of the iodine-containing compound in the crosslinking treatment solution is too high, the heat resistance of the resulting polarized film tends to decrease, although the reason is unclear. Conversely, if the concentration is too low, the effect of suppressing the dissolution of dichroic dyes tends to decrease. The concentration of the iodine-containing compound in the crosslinking treatment solution is preferably 1% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2% by mass or more. The concentration of the iodine-containing compound in the crosslinking treatment solution is preferably 6% by mass or less, more preferably 5.5% by mass or less, and even more preferably 5% by mass or less.
[0116] If the temperature of the crosslinking treatment solution is too high, dichroic dyes may dissolve, and the resulting polarizing film may exhibit uneven dyeing. Conversely, if the temperature is too low, the crosslinking effect may sometimes be reduced. The temperature of the crosslinking treatment solution is preferably 20°C or higher, more preferably 22°C or higher, and even more preferably 25°C or higher. The temperature of the crosslinking treatment solution is preferably 45°C or lower, more preferably 40°C or lower, and even more preferably 35°C or lower.
[0117] In addition to the stretching treatment described later, the PVA film can also be stretched separately during and between the above-mentioned treatments. This stretching (pre-stretching) prevents wrinkles from forming on the surface of the PVA film. From the viewpoint of the polarization performance of the resulting polarizing film, the total stretching ratio of the pre-stretching (the ratio obtained by multiplying the stretching ratios in each treatment) is preferably 4 times or less, more preferably 3.5 times or less, based on the original length of the PVA film before stretching. From the viewpoint of the polarization performance of the resulting polarizing film, the total stretching ratio of the pre-stretching is more preferably 1.5 times or more, based on the original length of the PVA film before stretching. The stretching ratio during the swelling treatment is preferably 1.1 times or more, more preferably 1.2 times or more, and even more preferably 1.4 times or more, based on the original length of the PVA film. The stretching ratio during the swelling treatment is preferably 3 times or less, more preferably 2.5 times or less, and even more preferably 2.3 times or less, based on the original length of the PVA film. The stretching ratio during the dyeing process is preferably 2 times or less, more preferably 1.8 times or less, and even more preferably 1.5 times or less, based on the original length of the PVA film. The stretching ratio during the crosslinking process is further preferably 1.1 times or more, based on the original length of the PVA film. The stretching ratio during the crosslinking process is preferably 2 times or less, more preferably 1.5 times or less, and even more preferably 1.3 times or less, based on the original length of the PVA film. The stretching ratio during the crosslinking process is further preferably 1.05 times or more, based on the original length of the PVA film.
[0118] (Stretching treatment)
[0119] The stretching treatment can be performed by either a wet stretching method or a dry stretching method. In the case of a wet stretching method, a solution containing a boron-containing compound such as boric acid (suitably an aqueous solution) can be used as the stretching treatment solution, and the stretching treatment can be performed in the stretching treatment solution, or in a dyeing treatment solution or a fixation treatment solution described later. Alternatively, in the case of a dry stretching method, a water-absorbing PVA film can be used to perform the stretching treatment in air. Of these, a wet stretching method is preferred, and uniaxial stretching in an aqueous solution containing boric acid is more preferred. When the stretching treatment solution contains a boron-containing compound, from the viewpoint of improving the stretchability of the PVA film, the concentration of the boron-containing compound in the stretching treatment solution is preferably 1.5% by mass or more, more preferably 2.0% by mass or more, and even more preferably 2.5% by mass or more. From the viewpoint of improving the stretchability of the PVA film, the concentration of the boron-containing compound in the stretching treatment solution is preferably 7% by mass or less, more preferably 6.5% by mass or less, and even more preferably 6% by mass or less.
[0120] The stretching treatment solution preferably contains iodine-containing compounds such as potassium iodide. If the concentration of the iodine-containing compound in the stretching treatment solution is too high, the resulting polarized film tends to have a noticeably bluish hue. Conversely, if the concentration is too low, although the reason is unclear, the heat resistance of the resulting polarized film tends to decrease. The concentration of the iodine-containing compound in the stretching treatment solution is preferably 2% by mass or more, more preferably 2.5% by mass or more, and even more preferably 3% by mass or more. The concentration of the iodine-containing compound in the stretching treatment solution is preferably 8% by mass or less, more preferably 7.5% by mass or less, and even more preferably 7% by mass or less.
[0121] If the temperature of the stretching treatment solution is too high, the PVA film tends to dissolve, soften, and easily break. Conversely, if the temperature is too low, the tensile properties tend to decrease. The temperature of the stretching treatment solution is preferably 50°C or higher, more preferably 52.5°C or higher, and even more preferably 55°C or higher. The temperature of the stretching treatment solution is preferably 70°C or lower, more preferably 67.5°C or lower, and even more preferably 65°C or lower. It should be noted that the preferred range of stretching temperature when performing stretching treatment by dry stretching is also as described above.
[0122] A higher stretching ratio during the stretching process results in a polarizing film with superior polarization properties; therefore, a ratio of 1.2 times or more is preferred, more preferably 1.5 times or more, and even more preferably 2 times or more. Furthermore, from the viewpoint of the polarization properties of the resulting polarizing film, the total stretching ratio (the ratio obtained by multiplying the stretching ratios in each process), including the aforementioned stretching ratio before stretching, is preferably 5.5 times or more, more preferably 5.7 times or more, and even more preferably 5.9 times or more, depending on the original length of the PVA film before stretching. There is no particular upper limit to the stretching ratio; however, if the stretching ratio is too high, the PVA film is prone to tensile breakage, so a ratio of 8 times or less is preferred.
[0123] There is no particular limitation on the method of stretching by uniaxial stretching; uniaxial stretching in the length direction or transverse uniaxial stretching in the width direction can be used. In the case of manufacturing polarizing films, from the viewpoint of obtaining materials with excellent polarization properties, uniaxial stretching in the length direction is preferred. Uniaxial stretching in the length direction can be performed by using a stretching device with multiple parallel rollers and varying the circumferential speed between each roller.
[0124] In this invention, the maximum stretching speed (% / min) during uniaxial stretching is not particularly limited, but is preferably 200% / min or higher, more preferably 300% / min or higher, and even more preferably 400% / min or higher. Here, maximum stretching speed refers to the fastest stretching speed in a given stage when stretching the PVA film using three or more rollers with different circumferential speeds in two or more stages. It should be noted that when stretching the PVA film in one stage without dividing it into two or more stages, the stretching speed in that stage is considered the maximum stretching speed. Furthermore, stretching speed refers to the increase in the length of the PVA film per unit time, relative to its original length before stretching, due to stretching. For example, a stretching speed of 100% / min means the speed at which the PVA film doubles in length within one minute from its original length. A higher maximum stretching speed allows for faster PVA film stretching (uniaxial stretching), resulting in increased productivity of the polarizing film, which is therefore preferable. On the other hand, if the maximum stretching speed becomes too high, excessive local tension may occur in the PVA film during the stretching process (uniaxial stretching), which can easily lead to tensile fracture. From this perspective, the maximum stretching speed is preferably no more than 900% / min.
[0125] (Cleaning process after dyeing)
[0126] After dyeing, it is preferable to clean the stretched PVA film. Cleaning is preferably performed by immersing the PVA film in a cleaning solution, or by blowing the PVA film with the cleaning solution. Water, for example, can be used as the cleaning solution. The water is not limited to pure water and may contain iodine-containing compounds such as potassium iodide. It should be noted that the cleaning solution may contain boron-containing compounds; in this case, the concentration of the boron-containing compound is preferably 2.0% by mass or less.
[0127] The temperature of the cleaning solution is preferably 5°C or higher, more preferably 7°C or higher, and even more preferably 10°C or higher. Furthermore, the temperature of the cleaning solution is preferably 40°C or lower, more preferably 38°C or lower, and even more preferably 35°C or lower. By maintaining the temperature of the cleaning solution at 5°C or higher, the breakage of the PVA film caused by water freezing can be suppressed. Additionally, by maintaining the temperature of the cleaning solution at 40°C or lower, the optical properties of the resulting polarizing film are improved.
[0128] Specific methods for producing a polarizing film include methods of subjecting a PVA film to a dyeing treatment, a stretching treatment, and a crosslinking treatment and / or a fixing treatment. As a preferred example, a method of sequentially subjecting a PVA film to a swelling treatment, a dyeing treatment, a crosslinking treatment, a stretching treatment (especially a uniaxial stretching treatment), and a washing treatment may be mentioned. In addition, the stretching treatment may be performed in any processing step before the above treatments, or may be performed in two or more multi-stages.
[0129] A polarizing film can be obtained by subjecting the PVA film that has undergone the respective treatments as described above to a drying treatment. The method of the drying treatment is not particularly limited, and examples thereof include a contact method in which the film is brought into contact with a heating roller, a method of drying the film in a hot air dryer, and a floating method in which the film is dried with hot air while being floated, and the like.
[0130] <Polarizing Film, Polarizing Plate>
[0131] To compensate for mechanical strength, the polarizing film of the present invention is produced by attaching a protective film to at least one surface. The polarizing film of the present invention is generally used by being attached with an optically transparent protective film having mechanical strength to form a polarizing plate. As the protective film, a triacetyl cellulose (TAC) film, a cellulose acetate-butyrate (CAB) film, an acrylic film, a polyester film and the like are used. Examples of the adhesive for attachment include PVA-based adhesives, urethane-based adhesives and the like, among which PVA-based adhesives are suitable.
[0132] The polarizing plate obtained by the above operation can be used as a component of an LCD by applying an acrylic-based pressure-sensitive adhesive or the like and then attaching it to a glass substrate. At the same time, it can also be attached to a retardation film, a viewing angle improving film, a brightness enhancement film and the like. Examples
[0133] The present invention will be specifically described by the following examples, but the present invention is not limited in any way by these examples.
[0134] <Calculation of MD Average Inclination Value, Phase Parameter (θ), and Average Inclination Value at ±200mm Positions>
[0135] The MD average inclination value, phase parameter (θ), and average inclination value at ±200mm positions of the PVA films obtained in the examples or comparative examples were calculated by the above methods. The results are shown in Table 1.
[0136] <Measurement of Swelling Degree of PVA Film>
[0137] Approximately 1.5 g of test piece was cut from the PVA film obtained in the following examples or comparative examples. The test piece was then immersed in 1000 g of distilled water at 30°C. After immersion for 30 minutes, the test piece was removed, the surface water was absorbed with filter paper, and its mass (We) was measured. Next, the test piece was placed in a hot air dryer and dried at 105°C for 16 hours, and its mass (Wf) was measured again. Based on the obtained masses We and Wf, the degree of swelling of the PVA film was calculated using the following formula.
[0138] Swelling degree (%) = (We / Wf) × 100
[0139] <Evaluation of the ultimate stretch ratio during stretching>
[0140] The ease of tensile fracture during stretching was evaluated based on the fracture ratio of the PVA film during the manufacturing of polarizing films in the following examples or comparative examples. Specifically, the fracture ratio of uniaxial stretching during 10 stretching processes in the manufacturing of polarizing films was measured, and the average value was taken as the ultimate tensile ratio, and the evaluation was performed according to the following criteria.
[0141] A… The maximum stretch ratio is 6.6 times or more.
[0142] B… The ultimate stretch ratio is 6.5 times or more but less than 6.6 times.
[0143] C… Ultimate stretch ratio is less than 6.5 times.
[0144] <Evaluation of the unevenness of polarizing plates>
[0145] The polarizing plate sample obtained by the method described in Example 1 was cut into 30cm × 30cm pieces and clamped between two polarizing plates (with a single-unit transmittance of 43.5% and a polarization degree of 99.9%) in a parallel Nicol prism configuration, such that the polarizing plates of the sample are orthogonal Nicol prisms relative to each other. A brightness of 40000 cd / m² was used. 2 The backlight is used to visually observe the optical polarization unevenness in the transmission mode, and the evaluation is carried out according to the following criteria.
[0146] A… uneven coloring exists.
[0147] B…No uneven coloring
[0148] [Example 1]
[0149] A film-forming stock solution (70% volatile content) was prepared by melt mixing 100 parts by weight of PVA (99.9 mol% saponification, 2400 degree of polymerization), 10 parts by weight of glycerol as a plasticizer, 0.1 parts by weight of lauric acid diethanolamide as a surfactant, and 233 parts by weight of water using a melt extruder. The solution was then sprayed from a T-die onto a support (surface temperature 98°C) to form a PVA film. When the moisture content of the sprayed PVA film reached 24%, the draw ratio was set to 1.10 by controlling the roller speed ratio, and the film was stretched. The film was then subjected to contact heat treatment at 105°C using the heat treatment roller in the latter half of the roll, resulting in a PVA film with a width of 5 μm and a thickness of 60 μm. It should be noted that regarding the moisture content during stretching, the PVA film is torn off between the stretching rollers, and after the mass (Ww) is measured, the film is placed in a hot air dryer and dried at 105°C for 16 hours, after which its mass (Wd) is measured. The moisture content of the film is calculated using the following formula.
[0150] Membrane moisture content (%) = (Ww - Wd) / Ww × 100
[0151] The obtained PVA film was cut into 650 mm wide pieces, and the film was subjected to swelling, dyeing, crosslinking, stretching, cleaning, and drying treatments in sequence to continuously manufacture polarizing films. The swelling treatment was performed by immersing the film in pure water (swelling solution) at 25°C while uniaxially stretching it to 2.00 times its original length. The dyeing treatment was performed by immersing the film in a potassium iodide / iodine aqueous dyeing solution (dyeing solution) at 32°C (potassium iodide / iodine (mass ratio) of 2:3, iodine concentration of 0.03–0.05% by mass) while uniaxially stretching it to 1.26 times its original length. In this dyeing treatment, the iodine concentration in the dyeing solution was adjusted within the range of 0.03–0.05% by mass so that the monomer transmittance of the polarizing film obtained after uniaxial stretching in the stretching treatment was within the range of 43.5% ± 0.2%. The crosslinking treatment was performed by immersing the edges in a boric acid aqueous solution (crosslinking treatment solution) at 32°C (2.6% by mass) while uniaxially stretching them 1.19 times along their length. The stretching treatment was performed by immersing the edges in a boric acid / potassium iodide aqueous solution (stretching treatment solution) at 55°C (2.8% by mass boric acid and 5% by potassium iodide) while uniaxially stretching them 2.00 times along their length. The cleaning treatment was performed by immersing the edges in a potassium iodide / boric acid aqueous solution (cleaning treatment solution) at 22°C (3-6% by mass potassium iodide and 1.5% by boric acid) for 12 seconds without stretching.
[0152] [Examples 2-4, Comparative Examples 1-3]
[0153] The manufacturing conditions of the PVA film were modified as shown in Table 1. Otherwise, the manufacturing and evaluation of the PVA film were performed in the same manner as in Example 1. It should be noted that the volatile fraction of the film-forming solution can be adjusted by adjusting the amount of water used for melt mixing in the melt extruder. The results are shown in Table 1.
[0154] Based on the above results, it can be seen that the color unevenness of the PVA film of the present invention is suppressed during the stretching process.
[0155] [Table 1]
[0156]
Claims
1. Polyvinyl alcohol film, wherein, Let F0(x) be the film thickness profile at position x in the MD direction, with any point on the film surface as the reference, and let F0(x) be the film thickness profile at position x in the MD direction, with a point 100 mm away from the aforementioned arbitrary point in the TD direction as the reference. -100 (x), let the film thickness profile at position x in the MD direction, with a point 200 mm from any of the aforementioned points in the TD direction as the reference, be F. -200 (x), let the film thickness profile at position x in the MD direction, with a point 100 mm away from any of the aforementioned points in the TD direction as the reference, be F. +100 (x), let F be the film thickness profile at position x in the MD direction, with a reference point at a point 200 mm away from any of the aforementioned points in the TD direction. +200 (x), let F'0(x) and F' be the differential values of the MD direction of each film thickness profile. -100 (x), F' -200 (x), F' +100 (x) and F' +200 (x), |F'0(x)|, |F' -100 (x)|、|F' -200 (x)|、|F' +100 (x) | and |F' +200 The average tilt value of F'0(x) in the MD direction is less than 0.02 μm / mm. The point where F'0(x) shows a minimum value is set as C. n (n=1,2,3…), |F' -100 (C n )-F'0(C n )|、|F' -200 (C n )-F'0(C n )|、|F' +100 (C n )-F'0(C n )|and|F' +200 (C n )-F'0(C n The phase parameter (θ) defined by the average value of ) | is above 0.015 μm / mm. The MD direction is the flow direction of the membrane, and the TD direction is the width direction of the membrane. The film thickness profile was obtained by measuring the film thickness at 1024 points per 1 mm. The average tilt value is calculated using the following equations (1) to (6). The phase parameter (θ) is a value defined by the following equations (7) to (12). In equations (1) to (6), k represents a function of x, namely F'0(x) and F'0(x). +100 (x), F' +200 (x), F' -100 (x), F' -200 Substituting the symbols 1 to 1024 into x in (x), k in (Equation 12) represents the value of k in C. n The function is λ(C) n ) for C n Substitute C1~C respectively n The symbol.
2. The polyvinyl alcohol film according to claim 1, wherein the width is 4m or more.
3. The polyvinyl alcohol film according to claim 1 or 2 has a swelling degree of 170~220%.
4. The polyvinyl alcohol film according to claim 1 or 2, wherein the thickness is 30 μm to 65 μm.
5. The polyvinyl alcohol film according to claim 1 or 2, wherein it is a film for manufacturing optical films.
6. The polyvinyl alcohol film according to claim 5, wherein, The optical film is a polarizing film.
7. A polarizing film, which is manufactured using the polyvinyl alcohol film according to any one of claims 1 to 6.
8. A polarizing plate, which is manufactured by attaching a protective film to at least one side of the polarizing film of claim 7.
9. A method for manufacturing a polyvinyl alcohol film according to any one of claims 1 to 6, comprising: forming a polyvinyl alcohol film using an aqueous solution of polyvinyl alcohol with a concentration of 32% by mass or less; stretching the polyvinyl alcohol film at a stretch ratio of 1.075 to 1.135 when the moisture content of the polyvinyl alcohol film is 20% by mass or more; and wherein the volatile content of the film-forming solution used in the film-forming process is 70% by mass or more.
Citation Information
Patent Citations
Polyvinyl alcohol-based film, manufacturing method of polyvinyl alcohol-based film and polarizing film
JP2017008298A
Polyvinyl alcohol-type polymer film and method for producing same
CN104169342A
Vinol series polymer film and its mfg. method
CN1696191A
Method for manufacturing polyvinyl alcohol film
JP2001315141A
